Local Knowledge On Plants - Esa, Norizan; Che Lah, Salasiah (Universiti Sains Malaysia, 2016)
The immense richness of the biodiversity of Malaysian flora has earned her a place as one of the twelve mega-biodiversity areas of the world. The local communities have long benefited from this biodiversity through various uses, as a result of their local knowledge of these flora. As such, efforts to document local knowledge regarding the flora and their uses, need to be intensified before this biodiversity become threatened or destroyed. To date, many parties have been involved in the preservation and conservation of the biodiversity of local flora. These include the establishment of a conservatory of living plants, documentation of species, known or previously newly discovered one, scientific investigations of various aspects of the local flora, as well as the manufacture of bioproducts based on the local flora. Some of the formulations of the bioproducts are also based on the local knowledge of certain communities. There are several bioproducts that has been succesfully commercialised, as a result of the research and development carried out by universities and certain government agencies. Sharing of these knowledge with the public has also been carried out, for example through environmental education activities, by various local agencies and organisations.